CEO duality and firm performance: Evidence from an exogenous shock to the competitive environment - Yang, Tina; Zhao, Shan (Journal of Banking & Finance, 2014)
Regulators and governance activists are pressuring firms to abolish CEO duality (the Chief Executive Officer is also the Chairman of the Board). However, the literature provides mixed evidence on the relation between CEO duality and firm performance. Using the exogenous shock of the 1989 Canada–United States Free Trade Agreement, we find that duality firms outperform non-duality firms by 3–4% when their competitive environments change. Further, the performance difference is larger for firms with higher information costs and better corporate governance. Our results underscore the benefits of CEO duality in saving information costs and making speedy decisions.